OPPORTUNITIES FOR THE DEVELOPMENT OF BEER TOURISM IN UKRAINE - LUSHCHYK, MARIYA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article describes the current state of development of beer tourism in Ukraine. In particular, the theoretical aspects of the development of beer tourism are studied: the ambiguity of approaches to the interpretation of the concept of beer tourism is pointed out; the subspecies of beer tourism are singled out and the main components of the beer tour are indicated in terms of their difference from other types of tours. The main variants of classifications of types of beer as the main product of beer tourism on the following signs are described: according to GOST 29018−91; GOST 3473-78, depending on the mass fraction of dry matter in the initial wort and the method of fermentation (the so-called international classification of beer). According to opinion polls, the key parameters of a typical portrait of the average beer consumer, and, consequently, a potential customer of a beer tour are given − gender, age, place of residence, consumer wealth, volume and location of consumption, preferences on type, price and packaging of beer. The economic indicators of the beer industry in Ukraine in the last decade are characterized: the causes and consequences of the beer crisis in Ukraine in 2013–2014, the activities and portfolios of beer brands of key players in the beer market of Ukraine − corporations SUN InBev Ukraine, Carlsberg Ukraine (Carlsberg Ukraine), Oasis CIS («First Private Brewery») and Obolon. The possibilities of craft brewing in Ukraine are analyzed, a brief description of the key craft breweries of Ukraine (VARVAR, PRAVDA Beer Theater, Collider, Tsypa Brewery, Bierwille, White Rabbit, Andrii’s Craft Brewery, K&F Brewery) is given. The information on top locations of beer tourism by regions and the main beer festivals and events of the country is systematized. Problems and perspective directions of development of domestic beer tourism are defined. It was found that the scale of beer tours in Ukraine is not well studied, however, with proper organizational work, beer tourism and, accordingly, beer tours in the country can significantly replenish the amount of tax revenues to local and state budgets, which will lead to effective policy and business revival. activity that will affect the national economy.
Keywords: beer tourism; beer; types of beer; craft; beer tour; beer festival; beer map